Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/jo402600b
|View full text |Cite
|
Sign up to set email alerts
|

Diazirine-Containing Photoactivatable Isoprenoid: Synthesis and Application in Studies with Isoprenylcysteine Carboxyl Methyltransferase

Abstract: Photoaffinity labeling is a useful technique employed to identify protein–ligand and protein–protein noncovalent interactions. Photolabeling experiments have been particularly informative for probing membrane-bound proteins where structural information is difficult to obtain. The most widely used classes of photoactive functionalities include aryl azides, diazocarbonyls, diazirines, and benzophenones. Diazirines are intrinsically smaller than benzophenones and generate carbenes upon photolysis that react with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…To improve understanding of the process of protein prenylation, as well as identify protein substrates that are lipidated through this process, synthetic small molecule analogues of the isoprenoids are being used. Photoactivatable [16,17] and fluorescent [18] isoprenoid analogues have been used to examine protein-protein interactions of the prenylated proteins and to develop convenient assays for prenyltransferase activity, respectively. In addition, there has been significant interest in identifying prenylated proteins via metabolic labeling using modified isoprenoid probes followed by enrichment and proteomic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…To improve understanding of the process of protein prenylation, as well as identify protein substrates that are lipidated through this process, synthetic small molecule analogues of the isoprenoids are being used. Photoactivatable [16,17] and fluorescent [18] isoprenoid analogues have been used to examine protein-protein interactions of the prenylated proteins and to develop convenient assays for prenyltransferase activity, respectively. In addition, there has been significant interest in identifying prenylated proteins via metabolic labeling using modified isoprenoid probes followed by enrichment and proteomic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…A number of these approaches rely on the use of chemically modified isoprenoid analogues that introduce bioorthogonal groups suitable for both in vitro and in vivo investigations (Wang & Distefano, 2016). Reports on functional groups used to modify isoprenoids include azides (Rose et al, 2005) and alkynes (Hosokawa et al, 2007) for copper-catalyzed cycloaddition (click) reactions, aldehydes for oxime ligation (Rashidian, Dozier, Lenevich, & Distefano, 2010) and photoactivatable benzophenones (Henry et al, 2009) and diazirines (Vervacke et al, 2014) for labeling of enzyme active sites. Some of these isoprenoid analogues have proved to be useful for biotechnology applications including enzymatic labeling for bioconjugation of proteins, DNA and nanostructures (Duckworth et al, 2007; Rashidian et al, 2013; Y.…”
Section: Introductionmentioning
confidence: 99%
“…The greater yield of photocrosslinked His-Ste14p, coupled with the ease of analysis achieved with the probe, suggested that this new class of isoprenoid analogues should be more widely used in studies of enzymes that act on terpene-derived molecules. 181 …”
Section: Applications Of Cmpal For Discovery Of Targets and Inhibitorsmentioning
confidence: 99%